Comparação entre os sistemas confinado e em piquete para suínos em crescimento e acabamento - Aldemir Alves Pereira , José; Vaz de Mello, Hélcio; Maia Cardoso, Edson; Ferreira de Freitas, Ari (Revista Ceres, 2025)
Thirty-six growing pigs (18 Duroc and 18 Duroc x Pietrain crosses) ranging from 80 to 92 days of age, and weighing on average of 18.4 kg were used to study the effects of drylot and pasture feeding on performance and carcass quality of animals at the Federal University of Viçosa. The following treatments were compared: 1. drylot feeding during growing and finishing phases; 2. pasture during the growing phase, and drylot feeding during the finishing phase; 3. pasture during both growing and finishing phases.